Kemitraan strategis untuk kesehatan masyarakat: mendukung eliminasi malaria di Sumatera Selatan - Nur Alam Fajar; Hamzah Hasyim; Iche Liberty; Esti Sri Ananingsih; Risa Nur Amalia (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Strategic Partnership for Public Health: Supporting Malaria Elimination in South Sumatra. Background: South Sumatra has significant potential for malaria elimination but faces challenges, including diverse ecosystems and socioeconomic factors. Strategic collaborations and a comprehensive, community-based approach are essential for successful intervention and long-term solutions. Purpose: This activity aims to increase community awareness and knowledge about malaria and its prevention; strengthen local capacity in early detection, treatment, and prevention of malaria; encourage active community involvement in vector control and surveillance efforts; and develop evidence-based policy recommendations for local governments. Method: The approach includes data analysis to create evidence-based treatments for successful malaria management, community focus groups to gauge attitudes toward the disease, stakeholder brainstorming sessions for vector control tactics, and GIS training seminars. Results: A post-implementation assessment showing a decline in cases suggests that the introduction of the malaria mobile health application has greatly raised community awareness and understanding about malaria, including its symptoms, risks, and preventative techniques. Furthermore, by enabling health professionals and policymakers to pinpoint high-risk regions, the GIS has improved efforts to prevent by facilitating data-driven intervention prioritization and more effective resource allocation.